Timing to surgery of Chiari malformation type 1 affects complication types: An analysis of 13,812 patients - Naessig, Sara (J Craniovertebr Junction Spine, 2020)
BACKGROUND: Chiari malformations (CM) are congenital defects due to hypoplasia of the posterior fossa with cerebellar herniation into the foramen magnum and upper spinal canal. Despite the vast research done on this neurological and structural syndrome, clinical features and management options have not yet conclusively evolved. Quantification of proper treatment planning, can lead to potential perioperative benefits based on diagnoses and days to procedure. This study aims to identify if early operation produces better perioperative outcomes or if there are benefits to delaying CM surgery. AIMS AND OBJECTIVE: Assess outcomes for Chiari type I. METHODS: The KID database was queried for diagnoses of Chiari Malformation from 2003-2012 by icd9 codes (348.4, 741.0, 742.0, 742.2). Included patients: had complete time to procedure (TTP) data. Patients were stratified into 7 groups by TTP: Same-day as admission (SD), 1-day delay (1D), 2-day delay (2D), 3-day delay (3D), 4-7 days delay (4-7D), 8-14 days delay (8-14D), >14 days delay (>14D). Differences in pre-operative demographics (age/BMI) and perioperative complication rates between patient cohorts were assessed using Pearson's chi-squared tests and T-tests. Surgical details, perioperative complications, length of stay (LOS), total charges, and discharge disposition was compared. Binary logistic regressions determined independent predictors of varying complications (reference: same-day). RESULTS: 13,812 Chiari type I patients were isolated from KID (10.12 ± 6.3, 49.2F%, .063 ± 1.3CCI). CM-1 pts were older (10.12 yrs vs 3.62 yrs) and had a higher Charlson Comorbidity Score (0.62 vs 0.53; all P < 0.05). Procedure rates: 27.8% laminectomy, 28.3% decompression, and 2.2% spinal fusion. CM-1 experienced more complications (61.2% vs 37.9%) with the most common being related to the nervous system (2.8%), anemia (2.4%), acute respiratory distress disorder (2.1%), and dysphagia (1.2%). SD was associated with the low length of stay (5.3 days vs 9.5-25.2 days, P < 0.001), total hospital charges ($70,265.44 vs $90, 945.33-$269, 193.26, P < 0.001) when compared to other TTP groups. Relative to SD, all delay groups had significantly increased odds of developing postoperative complications (1D-OR: 1.29 [1.1- 1.6] → 8-14D-OR: 4.77[3.4-6.6]; all P < 0.05), more specifically, nervous system (1D-OR: 1.8 [1.2-2.5] → 8-14D-OR: 3.3 [1.8-6.2]; all P < 0.05).Sepsis complications were associated with a delay of at least 3D(2.5[1.4-4.6]) while respiratory complications (6.2 [3.1-12.3]) and anemia (2 [1.1-3.5]) were associated with a delay of at least 8-14D (all P < 0.05).